PARTISIPASI MASYARAKAT DALAM PROYEK PENANGGULANGAN KEMISKINAN DI PERKOTAAN (P2KP) (Studi Kasus di Kecamatan Pedan Kabupaten Kiaten) - Suminah, Suminah; Anantanyu, Sapja; Wijianto, Arip (AGRITEXTS: Journal of Agricultural Extension, 2008)
This reseorch is survey which focusing in participation community in urban poorness at P2KP Program. The purpose ofthis research is to studi how Community participation in P2KP Program at Pedan Sub-District of Klaten District. Data were composed by: observation, interview technique with community, local elite, P2KP ojjicers, and stakeholders,Â· and studi document. Data were analysed by tabulation and statistic descriptive. The result shows that community participation in P2KP Program at Kaligawe Village in high category as according to each role because have given the contribution to attainment two from three target e. i.: (1) was establish BKM "Bina Sejahtera" in to promote development participation process by to facilitate in planning activities. The activities were decanted in PJM Pronangkis; and (2) opening in access of community services, specially poor population in Tridaya. This effort was supported by a Direct Community Fund (BLM) of P2KP and self-supporting of community.